Effects of a 12-Week Recreational Skiing Program on Cardio-Pulmonary Fitness in the Elderly: Results from the Salzburg Skiing in the Elderly Study (SASES) - David Niederseer (MDPI AG, 2021)
Objectives: To investigate whether recreational alpine skiing in the elderly can improve cardio-pulmonary fitness. Design: Randomized controlled study with pre–post repeated measurements. Methods: A total of 48 elderly participants (60–76 years) were randomly assigned to either participate in a 12-week guided recreational skiing program (intervention group, IG, average of 28.5 ± 2.6 skiing days) or to continue a sedentary ski-free lifestyle (control group, CG). Cardio-pulmonary exercise testing (CPET) and pulmonary function testing were performed in both groups before (PRE) and after (POST) the intervention/control period to compare parameters PRE vs. POST CPET. Results: At baseline, IG and CG did not differ significantly with respect to CPET and pulmonary function parameters. At POST, several measures of maximal exercise capacity and breathing economy were significantly improved in IG as compared to CG: maximal oxygen capacity (IG: 33.8 ± 7.9; CG: 28.7 ± 5.9 mL/min/kg; p = 0.030), maximal carbon dioxide production (IG: 36.2 ± 7.7; CG: 31.8 ± 6.5 mL/min/kg; p = 0.05), maximal oxygen pulse (IG: 16.8 ± 4.2; CG: 13.2 ± 4 mL/heart beat; p = 0.010), maximal minute ventilation (IG: 96.8 ± 17.8; CG: 81.3 ± 21.9 l/min; p = 0.025), and maximal metabolic equivalent of task (METs, IG: 9.65 ± 2.26; CG: 8.19 ± 1.68 METs; p = 0.029). Except for oxygen pulse, these significant changes could also be observed at the anaerobic threshold. Maximal heart rate and pulmonary function parameters remained essentially unchanged. Conclusion: Regular recreational skiing improves cardio-pulmonary fitness along with breathing economy and thus can contribute to a heart-healthy lifestyle for the elderly.